Effect of Physical Activity on Sclerostin Concentrations in Blood Serum - Luziani, Stefani; Candy, Helena; Raysa, Elisabeth; Juniari, Sri; Darma, Prahasari; Juhanna, Indira Vidiari; Adiatmika, I Putu Gede (Sport and Fitness Journal, 2022)
After entering adulthood, the quality and quantity of bone decreases with age. Bone metabolism is influenced by many factors and signaling pathways. Sclerostin is an antagonist of the Wnt signaling pathway in osteoblast lineage cells, thus causing a decrease in bone formation. Recent studies have shown that mechanical loading of the bones, for example by doing physical activity, can affect the concentration of sclerostin in blood serum. However, research on this topic still has wide variations in terms of frequency, intensity, duration, and the type of exercise that can cause changes in serum sclerostin concentrations. This study was conducted using the literature review method, we reviewed and compared the latest journals that discussed the relationship between physical activity and sclerostin concentrations in blood serum. Physical activity that decreases sclerostin levels in blood serum is physical activity that has been done regularly and carried out over a long period of time. Physical activity that is only done occasionally will increase the level of sclerostin in the blood serum, which will then decrease again over time to the level as before physical activity was conducted. In conclusion, certain physical activity has a good impact on bone health that can be evaluated with the levels of sclerostin and may be a marker of physical activity towards aging of bones.